2018
DOI: 10.1200/jop.17.00091
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Results of a Medicare Advantage Cancer Management Program

Abstract: A practice-based program supported by a payer sponsor can reduce costs while maintaining high adherence to treatment pathways and patient satisfaction in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Alternative payment models, such as the Centers for Medicare and Medicaid Services Oncology Care Model, 8,9 contain financial incentives to enhance clinic-based, ambulatory care systems and prevent avoidable hospitalizations. A number of cancer-focused delivery system innovations have shown promise for reducing hospitalizations during cancer treatment, including patient navigation programs, 10 proactive telephonic nursing, 11 and electronic systems for between-visit symptom reporting. 6,12 Many of these interventions are resource intensive, and targeting outreach interventions to patients at high risk for hospitalization has been identified as a key strategy for preventing unplanned hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative payment models, such as the Centers for Medicare and Medicaid Services Oncology Care Model, 8,9 contain financial incentives to enhance clinic-based, ambulatory care systems and prevent avoidable hospitalizations. A number of cancer-focused delivery system innovations have shown promise for reducing hospitalizations during cancer treatment, including patient navigation programs, 10 proactive telephonic nursing, 11 and electronic systems for between-visit symptom reporting. 6,12 Many of these interventions are resource intensive, and targeting outreach interventions to patients at high risk for hospitalization has been identified as a key strategy for preventing unplanned hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…18,26,32 All studies were in a single setting. Seven were longitudinal, 18,19,22,26,29,30,32 6 used a pre–post design, 17,20,24,25,27,28 2 were random control trials, 21,23 and 1 a retrospective review. 31 Half (n = 8) included a comparison group.…”
Section: Resultsmentioning
confidence: 99%
“…Six articles included patient- and/or caregiver-reported experience measures and clinical measures. 19,21,22,24,26,27 Five targeted patient and/or caregiver experiences captured through administrative data (rather than direct report) and clinical measures. 20,25,29,31,32 Two included all 3 types of measures: clinical, patient/caregiver-reported experiences, and patient/caregiver experiences captured through administrative data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the Medicare population, where patients are frailer and living with more comorbidities, a 3-year study of a practice-based, clinical pathways program coupled with a patient care-management program identified a cost savings of more than $3 million mainly due to a reduction in medication costs but also from a reduction in inpatient stays and emergency room visits. 5 The 2018 study concluded that "a practice-based program supported by a payer sponsor can reduce costs while maintaining high adherence to treatment pathways and patient satisfaction in older patients. "…”
Section: Pathways To Successmentioning
confidence: 99%